Daya Saing dan Foreign Direct Investment - Nairobi Nairobi; Fadeli Yusuf Afif (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
abroad and domestically. Incoming investment is affected by a country's daytime strength. Widespread investment encourages more competition and corrupt practices as many investors want to reduce the bureaucracy they face. However, in the investment market a high level of corruption also makes a country's economy unattractive. This study aims to analyze the effect of a country's competitiveness on the entry of Foreign Direct Investment in ASEAN. The variables used in this study are foreign investment, competitiveness, Corruption Perception Index, and political stability. The analytical method used is the Random Effect Model. This shows that state power is able to encourage direct foreign investment in a positive direction, as well as the Corruption Perception Index where the handling of the level of corruption will encourage the entry of Foreign Direct Investment. Political stability in this study does not have a significant effect, meaning that political shocks do not interfere with the entry of Foreign Direct Investment in ASEAN in the period 2010 to 2020.